Arboviruses isolated from mosquitoes collected from urban and peri-urban areas of eastern Australia - Jansen, Cassie C; Prow, Natalie A; Webb, Cameron E; Hall, Roy A; Pyke, Alyssa T; Harrower, Bruce J; Pritchard, Ian L; Zborowski, Paul; Ritchie, Scott A; Russell, Richard C; Van Den Hurk, Andrew F (Journal of the American Mosquito Control Association, 2009)
To determine the presence of arboviruses in mosquito populations from major urban areas of eastern Australia, a total of 67,825 mosquitoes, representing -60 species, was collected and tested from Cairns, Brisbane, and Sydney between January 2005 and April 2008. Mosquito pools were screened by inoculation onto mosquito cell cultures and the detection of viral antigen using a panel of flavivirus and alphavirus monoclonal antibodies in an enzyme-linked immunosorbent assay. Suspect positive samples were confirmed using virus-specific real-time reverse transcriptase-polymerase chain reaction assays. No flaviviruses were detected, but 2 alphaviruses were isolated from mosquito pools collected from Cairns, with 1 Barmah Forest virus isolate from a pool of 100 Aedes vigilax and 1 Ross River virus isolate from a pool of 83 Verrallina carmenti. In addition, a single Aedes alternans collected from Sydney yielded an isolate most similar to Stretch Lagoon virus, a newly described virus from the genus Orbivirus. These results suggest that during the study, arboviruses were circulating at a low level in the areas sampled. The findings from this study will promote public health awareness of the risk of arboviruses in urban areas, leading to more informative public health campaigns to safeguard the Australian public.